TUJUAN PENDIDIKAN BERBASIS AL-QUR’AN - Sari, Windy Dian (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2025)
This paper examines the verses of the Qur'an based on an expert understanding of the purpose of education. This article uses a descriptive qualitative approach. The results of the study showed that education is organized to educate each individual in his role as a servant of God, personal, part of the profession, part of society, citizen and citizen of the world. In the Qur'an, education aims to educate individuals to develop their potential. The Qur'an teaches that people are educated to have sufficient knowledge, good manners, qualified skills, and based on faith. The purpose of such education, is described by Islamic education experts who understand the verses of the Qur'an from various sides